2001
DOI: 10.1210/en.142.7.3075
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Angiotensin II Subtype 2 Receptor Induces Catecholamine Release in an Extracellular Ca2+-Dependent Manner through a Decrease of Cyclic Guanosine 3',5'-Monophosphate Production in Cultured Porcine Adrenal Medullary Chromaffin Cells

Abstract: We have previously demonstrated that CGP 42112 (AT(2) agonist > or =1 nM) markedly reduces catecholamine biosynthesis through AT(2), which is the major angiotensin II (AngII) receptor subtype in cultured porcine chromaffin cells. Also, we have shown that CGP 42112 (> or =1 nM) induces a reduction in cGMP production in these cells. The present study showed that AngII reduced cGMP production via AT(2) in a manner similar to that found with CGP 42112. AngII (1 nM) significantly increased catecholamine secretion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…However, the involvement of AT 1 and AT 2 receptors in such effect is also dependent on the animal species studied [6][7][8][9][10][11][12]. It has been shown that cultured porcine chromaffin cells secreted catecholamines in response to an AT 2 agonist [9], whereas other studies have shown that Ang II increases catecholamine release from bovine chromaffin cells through functionally active AT 1 receptors [12]. Interestingly, some investigations reported mixed population of Ang II receptors in adrenal medulla depending on the species studied; for instance, AT 2 receptors accounted for 95% of Ang II binding sites in rat adrenal medulla, and 5% of the remaining binding sites were AT 1 [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the involvement of AT 1 and AT 2 receptors in such effect is also dependent on the animal species studied [6][7][8][9][10][11][12]. It has been shown that cultured porcine chromaffin cells secreted catecholamines in response to an AT 2 agonist [9], whereas other studies have shown that Ang II increases catecholamine release from bovine chromaffin cells through functionally active AT 1 receptors [12]. Interestingly, some investigations reported mixed population of Ang II receptors in adrenal medulla depending on the species studied; for instance, AT 2 receptors accounted for 95% of Ang II binding sites in rat adrenal medulla, and 5% of the remaining binding sites were AT 1 [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that angiotensin II (Ang II) is able to stimulate catecholamine release from bovine, rat and porcine adrenal chromaffin cells [1][2][3][4][5][6][7]. However, controversy exists about whether AT 1 or AT 2 receptors are involved in this effect in several species [6 -12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that, in cultured porcine chromaffin cells, AT2 stimulation induces CA secretion by mobilizing Ca 2+ through voltage-dependent Ca 2+ channels without affecting intracellular pools and that these effects could be mediated by a decrease in cGMP production (Takekoshi et al, 2001). Worck and his colleagues (1998) have also speculated that angiotensin II through binding to both receptor subtypes (both AT1 and AT2) facilitates the sympathoadrenal reflex response by actions at several anatomical levels of the neural pathways involved in the sympathoadrenal reflex response elicited during insulin-induced hypoglycemia in conscious chronically instrumented rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, losartan, an AT1-selective antagonist inhibited the CA secretory responses by high potassium, a direct membrane depolarizer, as well as by Bay-K-8644, an activator of L-type Ca 2+ channels, which facilitates the influx of Ca 2+ into the cells. The observation that AT1-selective antagonist inhibited the CA secretion evoked by Bay-K-8644 was surprising, as Takekoshi et al (2001) have reported that removal of external Ca 2+ significantly suppressed either AngII plus CV-11974 (AT1 antagonist, 100 nM; which simulates specific AT2 stimulation) or CGP 42112 (AT2 agonist)-induced CA secretion in cultured porcine adrenomedullary chromaffin cells. It is unclear how the blockade of AT1 receptors results in the inhibition of secretion seen in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation